Sol–gel synthesis and characterization of lithium aluminate (L–A–H) and lithium aluminosilicate (L–A–S–H) gels. Issue 6 (6th September 2022) - Simon, Sebastian; Bertmer, Marko; Gluth, Gregor J. G.
Abstract: Hydrous lithium aluminosilicate (L–A–S–H) and lithium aluminate (L–A–H) gels are candidate precursors for glass‐ceramics and ceramics with potential advantages over conventional processing routes. However, their structure before calcination remained largely unknown, despite the importance of precursor structure on the properties of the resulting materials. In the present study, it is demonstrated that L–A–S–H and L–A–H gels with Li/Al ≤ 1 can be produced via an organic steric entrapment route, while higher Li/Al ratios lead to crystallization of gibbsite or nordstrandite. The composition and the structure of the gels was studied by thermogravimetric analysis, X‐ray diffraction, 27 Al and 29 Si magic‐angle spinning nuclear magnetic resonance, and Raman spectroscopy. Aluminium was found to be almost exclusively in six‐fold coordination in both the L–A–H and the L–A–S–H gels. Silicon in the L–A–S–H gels was mainly in Q 4 sites and to a lesser extent in Q 3 sites (four‐fold coordination with no Si–O–Al bonds). The results thus indicate that silica‐rich and aluminium‐rich domains formed in these gels.